Ovariohisterectomia por videocirurgia (via NOTES vaginal híbrida), celiotomia ou miniceliotomia em cadelas - de Souza, Fernando Wiecheteck; Brun, Maurício Veloso; de Oliveira, Marília Teresa; Feranti, João Pedro Scussel; Corrêa, Rose Karina Reis; Idalêncio, Renam; Duda, Naila Cristina Blatt; Quadros, Aparício Mendes; Huppes, Rafael Ricardo [UNESP] (FapUNIFESP (SciELO), 2014)
The elective ovariohysterectomy (OH) is the most frequent procedures performed in dogs. In this study was used three groups of seven animals each (GI, GII, and GIII) that was undergone to three elective OH techniques: (i) mini-celiotomy (Snook-hook technique), (ii) hybrid Natural Orifice Translumenal Endoscopic Surgery (NOTES), and (iii) celiotomy (conventional surgery). The surgical techniques were compared considering the surgery time, trans and postoperative complications, technical difficulties, postoperative pain, surgical bleedind and some vital parameters as: heart rate (FC), respiratory rate (f{hook}), rectal temperature, invasive blood pressure (PVI) and central venous pressure (PVC). The OH by hybrid vaginal NOTES was the technique with the lowest post-surgical discomfort score and the lowest surgical bleeding, although its surgical time was higher compared to the conventional and the hook (mini-celiotomy) modalities.
Ovariohysterectomy for videosurgery (hybrid vaginal NOTES), celiotomy or mini-celiotomy in bitches
Keywords: Canine; Castration; Laparoscopy; Minimally-invasive surgery